Optoplasmonic biosensor for lung cancer telediagnosis: Design and simulation analysis - Alemayehu Getahun Kumela; Abebe Belay Gemta; Alemu Kebede Hordofa; Tamirat Abebe Desta; Mulubirhan Dangish; Habtamu Dagnew Mekonnen (Sensors International, 2023)
Applying quantum technology to dispatch face-to-face medical activities has generated significant interest. Unfortunately, the work on remote medical treatment soliciting quantum medication and information processing techniques is hard to observe. In this research, we proposed the Mach–Zehnder interferometer (MZI) based optoplasmonic biosensors (OPBs) with two homodyne detectors for remote-based lung cancer detection using classical and quantum mechanical principles. From the classical basis (Drude-Lorentz model and Kretschmann configuration), the influence of silver nanoparticles (Ag NPs) layers and biomolecule concentration on the performance of biosensors has been investigated. The different types of cancer cells for CL1-5, A549, and HT-29 have been used to analyze the sensitivity, and 319, 332, and 365 (deg/RIU) have been achieved, respectively. In addition, from quantum mechanical principles, the biosignals were conveyed through quantum teleportation in the form of the quantum state of light via fiber optics cable to enable precise remote detection of lung cancer. The obtained sensitivity and teleportation fidelity clearly reveal, the best candidacy of the proposed optoplasmonic biosensor for lung cancer telediagnosis.